Hubungan Minat Terhadap Motivasi Lansia Dalam Menjalankan Kegiatan Spiritual Di Panti Sosial Tresna Werdha Budi Sejahtera Banjarbaru - Nina Rahmadiliyanii; Noorlatifah Noorlatifah; Rika Sertiana Oktami; STIKES Husada Borneo; Puskesmas Dalam Pagar, Kabupaten Banjar; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
According to the Central Board of Statistics in 2008 the number of residents in Indonesia for more than 200 million people, while 7,5% or 15 million people, is the elderly population. An activity will be highly dependent on a person's interest. Interest is a powerful motivator to perform an activity. This research aims to determine the relationship between the interest toward elderly motivation in conducting spiritual activities in Residence Of Tresna Werdha Budi Sejahtera, Banjarbaru . The approach used in this research is a quantitative research design using analytical methods. The entire elderly population living in Residence of Tresna Werdha Budi Sejahtera Banjarbaru February 2012 as 110 people. The research sample use random sampling as many as 52 people. The results obtained that is elderly interest performing spiritual activities mostly positive (59.6%), motivation elderly in performing spiritual activities mostly less (73.1%). There is a significant correlation between the interest toward elderly motivation in conducting activies for spiritual in residence of Tresna Werdha Budi Sejahtera Banjarbaru in 2013 (p = 0.003).With increasing motivation in worship so that seniors are more active follow religious activities such as lectures, prayers and have a better interpretation of their own life.